2003
DOI: 10.1097/00001756-200305060-00012
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral cerebellar lesions influence arm movements bilaterally

Abstract: Limb ataxia is seen as a sign of ipsilateral cerebellar dysfunction. However, imaging studies have shown a bilateral cerebellar activation during unilateral hand movements. We questioned whether unilateral cerebellar lesions affect pointing movements not only of the ipsilateral hand but also of the contralateral hand. Horizontal saccadic pointing movements of 10 patients with unilateral cerebellar infarctions (infarctions of the posterior inferior or superior cerebellar artery) were compared with those of 19 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Both human functional imaging studies (Cui et al 2000;Ellerman et al 1994;Jäncke et al 1999) and neurophysiological studies in monkey (Greger et al 2004;MacKay 1988;Soteropoulos and Baker 2008) support the view that unilateral movements can be influenced by the ipsilateral and contralateral cerebellum. Contralateral cerebellar contribution may be mediated through crossing of cerebellar output to M1 at the level of the thalamus as proposed previously (Immisch et al 2003) and/or via a small proportion of M1 output reaching ipsilateral muscles via different routes at cortical, subcortical, and spinal levels (Brus-Ramer et al 2009;Gerloff et al 1998;Noskin et al 2008). Recently it was suggested that in monkey cerebellar influence to the contralateral side may arise from direct connections of the cerebellar nuclei to the spinal cord (Soteropoulos and Baker 2008).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Both human functional imaging studies (Cui et al 2000;Ellerman et al 1994;Jäncke et al 1999) and neurophysiological studies in monkey (Greger et al 2004;MacKay 1988;Soteropoulos and Baker 2008) support the view that unilateral movements can be influenced by the ipsilateral and contralateral cerebellum. Contralateral cerebellar contribution may be mediated through crossing of cerebellar output to M1 at the level of the thalamus as proposed previously (Immisch et al 2003) and/or via a small proportion of M1 output reaching ipsilateral muscles via different routes at cortical, subcortical, and spinal levels (Brus-Ramer et al 2009;Gerloff et al 1998;Noskin et al 2008). Recently it was suggested that in monkey cerebellar influence to the contralateral side may arise from direct connections of the cerebellar nuclei to the spinal cord (Soteropoulos and Baker 2008).…”
Section: Discussionmentioning
confidence: 72%
“…With regard to bilateral prehensile deficits, an increasing amount of behavioral studies has shown that movement impairment following unilateral cerebellar damage is not restricted to the ipsilesional side (Boyd and Winstein 2004;Fisher et al 2006;Immisch et al 2003), paralleling data showing that hemispheric cerebral strokes can affect ipsilesional motor function (Hermsdörfer and Goldenberg 2002;Jones et al 1989). Both human functional imaging studies (Cui et al 2000;Ellerman et al 1994;Jäncke et al 1999) and neurophysiological studies in monkey (Greger et al 2004;MacKay 1988;Soteropoulos and Baker 2008) support the view that unilateral movements can be influenced by the ipsilateral and contralateral cerebellum.…”
Section: Discussionmentioning
confidence: 95%
“…17,20,34 Interestingly, the DN was the only common region affected in all examined patients in the study by Fisher et al, 17 whose findings suggest that the reasons for bilateral impairment could be found in the output fibers arising from the DN, namely the DRTT. Nonetheless, the neuroanatomical basis by which the cerebellar hemisphere can simultaneously influence bilateral cortical activity and limb motor performance is unclear.…”
Section: Discussionmentioning
confidence: 91%
“…26 Because the corticospinal fibers decussate once again, motor deficits related to unilateral hemispheric cerebellar lesions, such as strokes, hemorrhages, and tumors, would be expected to influence only the ipsilateral limbs. 13,30 Surprisingly, each cerebellar hemisphere clearly influences bilateral limb movements, as demonstrated by human functional magnetic resonance imaging (fMRI) studies, 12,14,22,25 human transcranial magnetic stimulation (rTMS) studies, 10,32 and human motor performance studies, 17,20,34 as well as neurophysiological studies 19,35,36 and experimental lesioning studies in monkeys. 4,7 Although the neuroanatomical basis of this phenomenon is not clear, 36 uncrossed projections from the DN to the ipsilateral RN and thalamus were demonstrated in monkeys, 9,40 a finding that provides a simple and elegant explanation of the bilateral motor influence of each cerebellar hemisphere.…”
mentioning
confidence: 99%
“…However, one conceivable explanation is the possibility of bilateral manifestation with unilateral cerebellar pathology. On the literature,16 the unilateral cerebellar infarction produced limb ataxia bilaterally. Furthermore, stimulation of the unilateral deep cerebellar nuclei in monkey showed a bilateral movement representation 17.…”
Section: Discussionmentioning
confidence: 99%